(3eHGOF GdbGfhf GdJLGQjs - (3YdjGf(B, (3GdTQja s; (3eMeO GdHGTG(B;(3QjGV GdMdHj(B;(3aGFb TbjQ(B, s ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2000)
(3eaghe h eUGOQ GdbGfhf GdJLGQj h GdJWQb Gdi GdGYeGd GdJLGQjI h GdJGLQ h GdeJLQ h GdYbhO GdJLGQjI ceG Je JfGhd GdTQcGJ h TQcI GdJVGef h TQcI GdJhUjI GdHSjWI h TQcI GdeMGUI h GdTQcGJ PGJ GdeSDhdjI GdeMOhOI h TQcI GdJhUjI HGdCSge h GdTQcI GdeSGgeI GdYGeI h GNjQG GdGhQGb GdJLGQjI h GdYedjGJ GdeUQajI(B.s
(3edGMb U(B.210 (3eQGLY U(B.251s
Keywords: (3GdbGfhf GdJLGQjs